Hukum Islam dalam Tradisi Lokal: Telaah Pemikiran TGH. M. Soleh Chambali tentang Haji - Adi Fadli (Universitas Islam Negeri Mataram, 2012)
Annually, millions of pilgrims do their Hajj pilgrimage. However, not all of them fully understand how to do it, what its inner and deep meanings, and what its philosophical wisdom. This article focuses on analysis on TGH. M. Soleh Chambali’s thoughts about pilgrimage in the local context of tradition of Lombok Sasaknese society. Through historical approach of content analysis, it reveals that the thoughts are more contextual and social fiqh based. It is expressed in his explanation of istiṭā‘ah concepts and other local ḥajj problems.